CARTOGRAPHIE DES POTENTIALITES EN EAUX SOUTERRAINES PAR L’UTILISATION DE L’ANALYSE MULICRITERE ET LES SIG : CAS DU DISTRICT DU DENGUELE (NORDOUEST DE LA CÔTE D’IVOIRE) - Hyann, Pinatibi; Naga, Coulibaly; Honoré, Coulibaly Talnan Jean; Issiaka, Savane (European Scientific Journal, ESJ, 2015)
Fresh water availability in rural areas of Côte d’Ivoire is a key factor in economic development, improvement of people’s living conditions and keeping them in rural areas. The Denguélé district which is one of the driest areas of the country, experiences frequently the departure of is young population. These youngs people who constitute the working population leave their areas because they are short of economic equipment. The aim of this study was the mapping of groundwater potential so that population will be supplied with enough water of good quality. The adopted methodology consisted of three steps. The first step consisted on mapping the different criteria related to groundwater study using SRTM and Landsat data, water points and hydro-climate data ,the second one dealed with the weighting of criteria using multicritaria analysis (MCA) and the third step consisted to realize water availability, accessibility and potentiality maps.